2019
DOI: 10.1111/jcmm.14846
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA H19 ameliorates myocardial infarction‐induced myocardial injury and maladaptive cardiac remodelling by regulating KDM3A

Abstract: Myocardial infarction (MI) remains the leading cause of morbidity and mortality worldwide, and novel therapeutic targets still need to be investigated to alleviate myocardial injury and the ensuing maladaptive cardiac remodelling. Accumulating studies have indicated that lncRNA H19 might exert a crucial regulatory effect on cardiovascular disease. In this study, we aimed to explore the biological function and molecular mechanism of H19 in MI. To investigate the biological functions of H19, miRNA‐22‐3p and KDM3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 43 publications
2
56
1
Order By: Relevance
“…Based on the above findings, we further explored the potential molecular mechanisms by which PIP exerted its protective effects against I/R injury and pyroptosis. miRNAs are a group of non‐coding RNAs and could repress target genes via direct bonding to 3′UTR of mRNA 10,27,28 . Previous studies indicated that PIP exerted pharmacological effects via miRNA‐dependent manners 16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above findings, we further explored the potential molecular mechanisms by which PIP exerted its protective effects against I/R injury and pyroptosis. miRNAs are a group of non‐coding RNAs and could repress target genes via direct bonding to 3′UTR of mRNA 10,27,28 . Previous studies indicated that PIP exerted pharmacological effects via miRNA‐dependent manners 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant adenoviral vector encoding miR‐383 and its negative control was obtained from GeneChem, Inc 3,27,28 . In brief, the entire coding region of miR‐383 was cloned into shuttle vector GV135 (Shanghai, GeneChem, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Atherosclerosis is the major cause of coronary artery disease, leading to myocardial ischemia and infarction (Barquera et al 2015 ; de Valk and Marx 1999 ). In addition to the regulation of vascular function, lncRNA-H19 has been suggested to participate in cardiomyocyte injury induced by ischemia/reperfusion (I/R) or infarction (Zhang et al 2020 ; Li et al 2019b ).…”
Section: Lncrna-h19 and Atherosclerosis-related Cardiac Dysfunctionmentioning
confidence: 99%
“…It was found that lncRNA-H19 expression is significantly decreased in the infarcted myocardium of mice, and overexpression of lncRNA-H19 in AMI mice reduces infarct size and improve cardiac function by activating autophagy (Zhou et al 2018 ). Using a rat model of AMI, Zhang et al revealed that lncRNA-H19 sponges miR-22-3p to ameliorate AMI-induced myocardial damage by upregulating lysine (K)-specific demethylase 3A (KDM3A) (Zhang et al 2020 ). It was also reported that lncRNA-H19 protects H9C2 cells against hypoxia-induced injury by sponging miR-139, which targets Sex determining region Y (SRY)-related high-mobility group box 8 (Sox8) (Gong et al 2017 ).…”
Section: Lncrna-h19 and Atherosclerosis-related Cardiac Dysfunctionmentioning
confidence: 99%
“…The ceRNA hypothesis suggests that lncRNA competitively binds with microRNAs through microRNA response elements (MREs) and inhibits the down-regulation of mRNA translation by miRNAs [12]. Moreover, the role of lncRNA-miRNA-mRNA ceRNA regulatory networks has been revealed in different diseases, such as chronic myeloid leukemia, cardiovascular diseases, diabetic cataract, and myocardial infarction [13][14][15][16], which might impact the prognosis of the diseases. However, on the basis of high-throughput sequencing and large samples, only a few literatures have reported the role of ceRNA in PAAD.…”
Section: Introductionmentioning
confidence: 99%